DIY Innovations in Quantum Physics: Proving Light Dualism with Photoelectric Effect and Double Slit Experiments - Hidayati, Annisa Khoirul; Izzulhaq, Azzafa; Oktamaypasha, Rias; Rini, Salsa Billa Indah (Jurnal Pendidikan dan Ilmu Fisika, 2024)
This research aims to prove the dualism of the nature of light with the photoelectric effect experiment and the double slit experiment using simple tools. The experimental analysis method was used for this research. The photoelectric effect experiment that has been carried out successfully proves that light behaves as a particle, this is evidenced by f> f0, light emitted as small particles called photons. The double slit experiment conducted with one of the wave properties, namely interference, also proved that light behaves as a wave, resulting in the formation of dark and bright patterns. Both experiments can be conducted using simple tools, despite the limited facilities of the laboratory, so this experiment can still be done by utilizing existing tools and materials as an alternative.